European Federation for Medical Informatics – the Most Influential Promoter of Medical Informatics Development for the Past 45 Years - Masic, Izet (Acta informatica medica, 2021)
Medical informatics, as much as it is a result of evolution as planned philosophy, have its roots in the history of information technology and medicine. Development of medical informatics started in the fifties of the 20th century. In the period after Second World War USA was the leading country in the field of Computer science and the leader in using the first computers in medicine and healthcare services. The development of information and communication technologies (ICT) during the last two decades of 20th century was particularly important for development of medical informatics, with great influence of Internet by medical professionals at every level of health care system. Comprehensive and essential contents on medical informatics, but also the aspects nurtured by the main „schools of Medical informatics" - Anglo-Saxon (Abbot, Anderson, etc.), French (Gremy, Remond, etc.), German (Reichhertz). et al.), American (Collen, Green, et al.), Middle and East Europe (Dezelic, Masic, Zvarova, Naszlady, Mihalas, etc.), whose terms „Health Informatics" (Abbot) and „Medical Informatics" (Gremy and Reichertz) have entered the European and world medical literature. For those studying the subject or working in the field, the experiences of others who use Information and Communication Technologies (ICTs) for the better of health care can provide a necessary perspective. In promotion and spreading the knowledge and experiences of the medical informatics as scientific and academic discipline in the world, great impact was given by IMIA and its „branch associations" at every continent. But, most influential association became European Federation for Medical Informatics (EFMI), established on September 11th 1976 in Copenhagen with members of 10 national representatives (Barry Barber (UK), Antonio Perens de Talens (Italy), Francois Grémy (France), Rolf Hansen (Norway), Mogens Jorgensen (Denmark), Hans Peterson (Sweden), Peter Leo Reichertz (Germany), Jan Roukens (Netherlands), Jan van Egmond (Belgium) and Ilkka Vaananen (Finland) who adopted Statute of EFMI and other documents and prepared the first MIE Conference in Cambridge (UK) in 1978. Today EFMI represent leading European medical informatics professional organization representing 28 European countries and institutional members. EFMI is organized as a non-profit organization concerned with the theory and practice of Information Science and Technology within the Health and Health Sciences sector, in a European context. The goals set of EFMI are: a) To advance international co-operation and dissemination of information in Medical Informatics on a European basis; b) To promote high standards in the application of medical informatics; c) To promote research and development in medical informatics; d) To encourage high standards in education in medical informatics; and e) To function as the autonomous European Regional Council of IMIA. Author of this article described the facts about important events which EFMI, with contribution of national societies, members of EFMI, organized during 45 years of existence, including important facts about the influential medical informatics experts. Finally, author shortly described important facts about history of development of Health informatics in Bosnia and Herzegovina and South-Eastern Europe, including facts about his activities during long period of his participation in IMIA General Assembly and EFMI Council. There he was very actively involved in a lot of activities, including organization of 22nd MIE Conference in Sarajevo in 2009.